Penser la forêt : aux racines du non-aménagement des forêts uruguayennes - Pierre Gautreau (VertigO)
The concrete practices of forest management and texts about sylvicultural issues concerning today's territory of Uruguay (South America), have been analysed together throughout the XVIIIth-XXth centuries. The aim of the paper is to understand why today's native forests are left unmanaged in spite of evidence of historical experiments carried out in the past. Part of the answers can be found in the impact of international sylvicultural and preservationist models during the XXth century, as well as in the deep influence of the European and North-American approach on the uruguayan forestal institutions ; finally in the limited territorial analysis of the country and its real forestal development capacities. Theses points would be responsible of the incapacity of the country to create a genuine forestal developement model, which would allow for a management adapted to native forests.